Eksperimentasi Model Pembelajaran Student Team Achievment Devisions (STAD) Berbantuan Geogebra pada Materi Similaritas Ditinjau dari Gaya Belajar - Wawan wawan (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2017)
The objective of this article was to investigate the effect of learning model of STAD geogebra viewed from learning style. This article used the quasi experimental research method with the design factorial. The samples of the research were taken by using the cluster random sampling technique. The subject contained 26 students in experiment class and 24 students in the control class. The data was analyzed by using the two-way analysis of variance. The conclusions of this research that (1) the cooperative learning model of STAD geogebra type resulted in a better learning achievement in mathematics than the power point-assisted direct learning model (2) students with visual learning style have the same achievement with students with auditory learning styles. Students with auditory learning style have the same achievement with students with kinesthetic learning styles. Students with visual learning styles have a better academic achievement than students with kinesthetic learning styles and (3) difference in achievement of each learning method was not consistent with their respective learning styles and differences between individual learning style also was not consistent in each learning method